Etica, ciência e utilitarismo. - T Ribeiro (Acta Médica Portuguesa, 1997)
We begin this article with the distinction between Deontology, Moral and Ethics. We also review the concept and the relevance of Bioethics, as the "science of survival", and as part of Ethics, a section of Philosophy. We tried to answer two further questions considering the role of Science in orienting Ethics, or the possible place of utilitarianism in controlling Ethics. The author discusses some new aspects of the doctor/patient relationship, and their evolution in the last 100 years, as well as the relations between patients and Health care institutions. Some ethical problems were also raised related to the beginning and the end of life. Finally the author reflects on the difficulties of defining ethical concepts in the near future.